Vertical shear injuries: is there a relationship between residual displacement and functional outcome? - Nepola, J V; Trenhaile, S W; Miranda, M A; Butterfield, S L; Fredericks, D C; Riemer, B L (The journal of trauma, 1999)
Residual vertical displacement is often cited as being related to poor outcome in patients with pelvic injuries. This study attempts to clarify the relationship between residual vertical displacement and functional outcome. From 1982 to 1989, over 500 patients with pelvic ring injuries were treated at two Level I trauma centers. Thirty-three patients with vertical shear (Tile C) fractures and residual displacement (2-52 mm) were evaluated. Outcomes were quantified by using SF-36 Short-Form Health Survey (SF-36) and the Iowa Pelvic Score (IPS). There was no correlation between IPS or SF-36 scales and residual vertical displacement. The IPS correlated (p<0.05) with seven of eight SF-36 categories, excluding mental health. Patients reporting limp and leg length discrepancy also correlated with the IPS and select SF-36. Pelvic injuries showed no correlation between functional outcome and residual vertical displacement suggesting other factors. The degree of residual vertical displacement does not affect functional outcome.